Pendugaan Umur Simpan Tepung Jamur Tiram Putih (Pleurotus ostreatus) Pada Kemasan Plastik Polietilen dengan Metode Akselerasi - Sussi Astuti; Sri Setyani; Suharyono Suharyono; Muhammad Nurreza Nurreza H (Politeknik Negeri Lampung., 2019)
The aim of the research was to determine the shelf life of white oyster mushroom flour in polyethylene plastic packaging with the Arrhenius method. The study was arranged descriptively with two replications. White oyster mushroom flour was stored at three storage temperature conditions, i.e. 30oC, 40oC and 50o C in polyethylene plastic packaging with a thickness of 0.03 mm and stored for one month (28 days). Observations were made on water content, levels of free fatty acids, protein content, flavour and color of white oyster mushroom flour every once a week i.e. on days 0, 7, 14, 21 and 28. The data obtained were used to determine the shelf life of white oyster mushroom flour using acceleration (accelerated storage) method with Arrhenius equation model using Microsoft Excel software. The results showed that the shelf life of white oyster mushroom flour in polyethylene plastic packaging thickness of 0.03 mm using the Arrhenius method was set at a temperature of 30o C based on the parameters of the zero reaction protein content, which was 130.67 days (4.3 months). White oyster mushroom flour in polyethylene plastic packaging thickness of 0.03 mm during storage temperature of 30o C, 40o C, and 50o C tends to decrease protein content, color and aroma, but experience an increase in free fatty acid levels. White oyster mushroom flour in polyethylene plastic packaging at 30o C tends to increase in water content during storage, and decreased water content at 40o C and 50o C.